Evaluasi Kesesuaian Lahan Tanaman Padi, Palawija, dan Hortikultura Jenis Sayuran pada Subak di Desa Penyaringan dan Tegal Cangkring Kecamatan Mendoyo, Kabupaten Jembrana - ALDIYO BARUS; I NYOMAN DIBIA; I GUSTI PUTU RATNA ADI (Program Studi Agroekoteknologi, Fakultas Pertanian, Universitas Udayana, 2020)
Evaluation of Land, Palawija, and Horticultural Vegetable Land Suitability in Subak in Penyaringan and Tegal Cangkring Village in Mendoyo District, Jembarana Regency This study aims to determine the suitability of land for lowland rice, crops (maize and soybeans) and horticultural crops of vegetable species (onion and chili), determine the limiting factors for the plants being evaluated, and determine the direction of land use. Data obtained to complete the subak land resource database in Penyaringan Village and Tegal Cangkring Village. This research was conducted in December 2019-March 2020 using the land evaluation survey method. The stages of the research consisted of literature study, secondary data collection, delineation of homogeneous land units (SLH), determination of sample points, preliminary surveys, field surveys and soil sampling, analysis of soil samples in the laboratory, tabulation and interpretation of data, evaluation of land suitability and determining direction land use. The characteristics and quality observed were temperature, water availability (annual rainfall and dry month), humidity, root media (drainage, texture, rough material, effective depth), nutrient retention (soil CEC, KB, pH, and C-Organic) , nutrient availability (N, P, K), toxicity (salinity), erosion hazard, flood hazard, land preparation. The actual land suitability for rice plants is classified as S2-N, corn is classified as S3, soybeans are classified as N, shallots are classified as N, and chili is classified as S3. The limiting factor was improved suitability of potential land for rice plants classified as S1, corn classified as S2, soybeans classified as S3, shallots classified as S3, and chili classified as S3. Commodity order in land use in the study area: top priority for rice plants, second priority for corn and chilli plants, third priority for soybean and shallot plants.